The Effect of The Spread Of Covid-19 On International Trade And The Country’s Political, Social, And Economic Differences (Journal of Business and Management, 2022)
The COVID-19 pandemic has changed the world in an unprecedented way. The spread of COVID-19 can have an impact on international trade and the political, social, economic differences in each country. This study aims to determine how much influence the spread of COVID-19 has on international trade and to find out how much influence the spread of COVID-19 has on political, social, and economic differences in each country. The data was processed using the Partial Least Square (PLS) approach. PLS is a predictive technique that is an alternative to Ordinary Least Square (OLS), Canonical Correlation, or Structural Equation Modeling (SEM). The results of the study found that (1) The spread of COVID-19 had a significant effect of 34.8% on international trade. (2) The spread of COVID-19 has a significant effect of 44.8% on the country's political, social, and economic differences.Keywords: COVID-19, International Trade, politics, social and economy of the country, Partial Least Square